Stability analysis of analytical hierarchy process clustering protocol in mobile ad hoc networks. (11th May 2010) - Francis, Sharmila Anand John; Rajsingh, Elijah Blessing
Clustering the mobile ad hoc network is a fundamental problem that has been solved by many different approaches. Efficient and stable clustering always depends on choosing an appropriate cluster head in the network. This article proposes a novel efficient AHP clustering protocol called AHPC protocol that employs a powerful analytical hierarchy process methodology. Analytical hierarchy process methodology is a mathematical model that computes relative weights for all the mobile nodes in the network that facilitates the choosing of appropriate cluster heads in the network. The 11 essential factors of the mobile nodes are identified that influence the choosing of cluster heads. The mathematical and experimental analysis of AHPC protocol has been carried out. The results show that the proposed clustering protocol enhances the stability of the network by reducing the frequent cluster head changes, dominant set updates to a great extent, leading to a highly stable clustering protocol in mobile ad hoc networks.